Structural, electrochemical, electronic, and magnetic properties of monoclinic LixV2(PO4)3 for x = 3, 2, 1 using first-principles calculations - Ahmani Ferdi, Chouaib; Belaiche, Mohammed; Iffer, Elabadila (Journal of solid state electrochemistry, 2021)
Monoclinic lithium vanadium phosphate Li 3 V 2 (PO 4 ) 3 is a very promising cathode candidate for applications in Li-ion batteries, with a high operational voltage (~ 4 V vs. Li + /Li) and a high theoretical capacity of 197 mAh/g. However, the underlying electrochemical mechanism of monoclinic Li 3 V 2 (PO 4 ) 3 is not yet fully understood, due to its complexity. To gain more knowledge about the electrochemical performance of the monoclinic Li 3 V 2 (PO 4 ) 3 , we perform density functional calculations of structural, electrochemical, electronic, and magnetic properties of Li x V 2 (PO 4 ) 3 for x = 3, 2, 1, based on the full-potential linearized augmented plane wave (FP-LAPW) method. The generalized gradient approximation corrected with the present work self-consistently calculated Hubbard parameter U (GGA+U method) shows that it can successfully reproduce the experimental average lithium intercalation voltage for the redox couple V 4+ /V 3+ within 7% error, and within 2% error for the transition x : 3 ➔ 2. The present work method is fully ab initio and without any arbitrary parameters. In the literature, the existence of charge ordering in Li 2 V 2 (PO 4 ) 3 is subject to discrepancy. By analyzing the present calculated structural, magnetic, and electronic properties of Li 2 V 2 (PO 4 ) 3 , the existence of charge ordering had been confirmed. The present work method sets the path for accurately predicting the redox potential of future lithium and sodium phosphate compounds for the next-generation batteries technology.